Predicting Structural Details of the Sodium Channel Pore Basing on Animal Toxin Studies - Tikhonov, Denis B.; Zhorov, Boris S. (Frontiers in Pharmacology, 2018)
Eukaryotic voltage-gated sodium channels play key roles in physiology and are targets for many toxins and medically important drugs. Physiology, pharmacology and general architecture of the channels has long been the subject of intensive research in academia and industry. In particular, animal toxins such as tetrodotoxin, saxitoxin and conotoxins have been used as molecular probes of the channel structure. More recently, X-ray structures of potassium and prokaryotic sodium channels allowed elaborating models of the toxin-channel complexes that integrated data from biophysical, electrophysiological, and mutational studies. Atomic level cryo-EM structures of eukaryotic sodium channels, which became available in 2017, show that the selectivity filter structure and other important features of the pore domain have been correctly predicted. This validates further employments of toxins and other small molecules as sensitive probes of fine structural details of ion channels.